STUDENTS' PERCEPTION ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION: A Case Study at One of Public Senior High School in Bandung, West Java - Surya Handini, Astari (2014)
ABSTRACT The present study investigates the students' perception towards the use of English as a medium of instruction. This study, thus, explore the influences of English as a medium of instruction on classroom interaction. The data were collected through classroom observation, interviewing ten students who were chosen randomly and giving the questionnaire to whole students in a science program class. The basic framework of English as a medium of instruction was proposed by Schutzehofer and Mathelitsc (2009). The data from the interview were transcribed and interpreted to answer the research questions. The classroom observation data was supported by fulfilling the classroom observation sheet which was adopted from Joyce, Bruce, and Weil (1992). For analyzing the questionnaire, Likert Scale was applied in gaining the result. Based on the students' interview, this study reveals that 88,9% students had positive perception towards the use of English as a medium of instruction. The data was supported by the result of the questionnaire that almost all of students gave their positive perceptions to the use of English as a medium of instruction in the classroom. The influences of English as a medium of instruction were also revealed in the students' positive attitudes. Based on the classroom observation, most students were active, serious, and enjoying the teaching and learning process. The data was supported by findings from the students' interview that eight of nine students felt the positive influences towards the use English as a medium of instruction. Based on the findings, it is recommended that teachers can implement the English as a medium of instruction in developing students' English ability and students' interaction in the classroom. Keywords: English as a Medium of Instruction, Perception, Language Learning, Students' Achievement.